Developing Interactive Educational Game on The Students’ Speaking Ability at SMP Negeri 4 Gunungsitoli Selatan - Enjel Tris Jelita Telaumbanua; Hidayati Daeli; Afore Tahir Harefa; Yasminar Amaerita Telaumbanua (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This research aimed to develop an interactive educational game to improve students’ English speaking skills, focusing on the topics of Past Events and No Littering. The study employed the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through classroom observation, semi-structured interviews with teachers and students, questionnaires, expert validation sheets, and speaking performance tests. The speaking tests were administered in the form of pre-test and post-test, using oral tasks such as short monologues and guided dialogues that assessed fluency, pronunciation, vocabulary, and grammatical accuracy. The interactive educational game was developed using the Wordwall platform and integrated game-based learning features to promote active participation, motivation, and meaningful speaking practice. The results of media and material expert validation indicated that the product achieved a “Very Good” category with an average feasibility score of 90%. Statistical analysis of students’ speaking performance showed an improvement in the mean score from the pre-test to the post-test, indicating a positive effect of the game on students’ speaking ability. In addition, students’ responses during the implementation phase revealed high levels of engagement and motivation. Based on these findings, the developed interactive educational game is feasible and effective as a supplementary learning medium for enhancing students’ English speaking skills. Future research is recommended to apply the game on a larger sample and over a longer period, as well as to integrate similar game-based media into other English language skills such as listening or writing.